Combined Effects of Plyometric Exercise with Dynamic Taping and Kinesio Taping On Muscle Power, Speed, And Muscle Strength Among University Male Football Players – A Randomized Controlled Trial: Life Sciences-Physiotherapy - Rengaramanujam, Kanagaraj; Subbiah, Dr S.; A. Alahmari, Dr Khalid (International Journal of Life Science and Pharma Research, 2023)
Plyometric exercise (PE) is a high-intensity, short-duration training method that may offer an adequate stimulus toimprove physical fitness and sport-specific performance. The sports medicine team employs KT tapes in isolation or in conjunctionwith workout regimens to enhance athletic performance. Research has been done to find out the combined effects of plyometricswith various elements to improve sport-specific fitness performance among football players. More research needs to be examiningthe collective impact of plyometrics in conjunction with taping on fitness performances. The present randomized controlled trialstudy aims to determine the combined effect of plyometrics with dynamic taping (DT) and kinesio taping (KT) to improve musclepower, speed, and muscle strength among university football players. Forty-five university male football players between 18 and25 who fulfilled the inclusion criteria were randomly assigned to 1 of 3 groups (DT, KT, and control groups). Athletes performedPE for 6-weeks. Outcomes were measured at baseline and six weeks post-PE. Vertical jump, standing long jump, and single leg hoptests were used to measure muscle power, and the 30-meter sprint and strength dynamometers were used to measure speed andmuscle strength, respectively. Significant differences were found in the group receiving PE and DT than the other groups in all theoutcome variables (p<0.05). The combined effects of PE and DT significantly affect muscle power, speed, and muscle strengthamong university male football players compared to KT with PE and PE alone.